Sebuah Kajian Literatur Tentang Pengalaman Pasien Kanker Dalam Menghadapi Pandemi Covid-19 - Made Satya Nugraha Gautama; Surya Wahyuni; Muflihul Huda; Istiqomah Nur Khasanah; Ulfa Hikmawati; Slamet Aminanto; Stefany Putri Sahureka; Orin Juliastuty Terawati Rizal (Fakultas Keperawatan Universitas Andalas, 2023)
The COVID 19 pandemic has caused various problems for cancer patients. Complaints related to changes in the medication process to the high risk of contracting COVID-19. This qualitative literature study aims to find out what the experiences of cancer patients are like during the COVID-19 pandemic. Articles were searched through Sciencedirect, Sage, Pubmed, and Scopus databases. Keywords using the PCC approach (Population (or participants)/Concept/Context) namely population